2011
DOI: 10.1007/s11434-011-4631-8
|View full text |Cite
|
Sign up to set email alerts
|

An infectious clone of the highly pathogenic porcine reproductive and respiratory syndrome virus: Topology of glycoprotein 3 (GP3) addressing the intrachain disulfide bonds

Abstract: The highly pathogenic porcine reproductive and respiratory virus (hpPRRSV) with discontinuous 30 amino acid (aa) deletion as a gene marker has caused great economic loss in pig industry and since 2007 has become the dominant strain prevalent in China and Vietnam since 2007. Reverse genetics method is a powerful tool urgently needed to be used on the hpPRRSV to study the intriguing molecular mechanism of transcription, replication and the virulence determinant factors. In our study, we successfully constructed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 36 publications
(53 reference statements)
0
2
0
Order By: Relevance
“…ORF3 of PRRSV encodes the GP3 protein, which shows approximately 54% to 60% amino acid identity between North American and European isolates. In addition, GP3 can accommodate cysteine mutations and influence the reproductive capacity of PRRSV [ 9 ]. Experiments using a specific monoclonal antibody against the GP3 protein of the LV strain suggested that the GP3 protein is inserted into the virus particle or is a virus envelope-associated protein [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…ORF3 of PRRSV encodes the GP3 protein, which shows approximately 54% to 60% amino acid identity between North American and European isolates. In addition, GP3 can accommodate cysteine mutations and influence the reproductive capacity of PRRSV [ 9 ]. Experiments using a specific monoclonal antibody against the GP3 protein of the LV strain suggested that the GP3 protein is inserted into the virus particle or is a virus envelope-associated protein [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…GP5 has six epitopes that can induce specific neutralizing antibodies. The neutralizing ability of the antibodies is stronger than those induced by GP4 [ 2 , 9 , 11 ].…”
Section: Introductionmentioning
confidence: 99%